2020
DOI: 10.3390/ijerph17217962
|View full text |Cite
|
Sign up to set email alerts
|

Use of Non-Cancer Medications in New Zealand Women at the Diagnosis of Primary Invasive Breast Cancer: Prevalence, Associated Factors and Effects on Survival

Abstract: Background: Assessing the use of multiple medications in cancer patients is crucial as such use may affect cancer outcomes. This study reports the prevalence of non-cancer medication use at breast cancer diagnosis, its associated factors, and its effect on survival. Methods: We identified all women diagnosed with primary invasive breast cancer between 1 January 2007 and 31 December 2016, from four population-based breast cancer registries, in Auckland, Waikato, Wellington, and Christchurch, New Zealand. Throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…There was no significant difference in the proportion of molecular subtype distribution in MIBC compared to single focal breast cancer (24). A study showed that the proportion of distribution of different molecular subtypes in breast cancer was 68.7% in luminal subtype, 14% in HER2positive subtype, and 10.3% in triple negative subtype (25). In contrast, in our study, after excluding patients with missing or unclear values, 87.3% of patients were luminal subtype, 4.13% were HER2-positive subtype, and 8.54% were triple-negative subtype.…”
Section: Discussionmentioning
confidence: 97%
“…There was no significant difference in the proportion of molecular subtype distribution in MIBC compared to single focal breast cancer (24). A study showed that the proportion of distribution of different molecular subtypes in breast cancer was 68.7% in luminal subtype, 14% in HER2positive subtype, and 10.3% in triple negative subtype (25). In contrast, in our study, after excluding patients with missing or unclear values, 87.3% of patients were luminal subtype, 4.13% were HER2-positive subtype, and 8.54% were triple-negative subtype.…”
Section: Discussionmentioning
confidence: 97%